ESG performance and bank valuation - The influence of the COVID-19 pandemic on the ESG-value relationship - Hart, Harry (Cranfield University, 2025)
The thesis examines the relationship between Environmental, Social, and Governance (ESG) performance and banks’ valuation metrics, with a focus on how the COVID-19 pandemic impacted this relationship. The fixed-effects panel regression model, using a sample of 71 publicly listed banks across 29 OECD countries from 2015 to 2023, assesses the impact of overall and individual pillar ESG scores on three valuation and performance metrics. These metrics are the Price-to-Book (P/B) ratio, Return on Assets (ROA), and the Price-to-Earnings (P/E) ratio. The results of the pre-crisis period suggest no statistically significant relationship between ESG performance and valuation. However, COVID-19 had an influence, with results portraying a positive and statistically significant relationship between ESG performance and the P/B ratio and ROA in the post-COVID period. This suggests that investors priced in the resilience impact of strong ESG performance for banks with stronger sustainability during periods of market stress. Further analysis also indicated the ESG effect on valuations was primarily driven by the environmental and governance pillars, with the social pillar remaining statistically insignificant. The results also revealed a non-linear relationship between ESG scores and valuations, with the resilience of the ESG effect being more pronounced for smaller banks. This study contributes to sustainable finance literature, providing evidence for sector-specific relationships between ESG and value in the banking industry. The results provide important considerations for banks, investors, and regulators, since a strong ESG performance is no longer an asset for reputation but a strong indicator for resilience in banks, especially during periods of crisis.
Keywords: ESG; bank valuation; COVID-19; sustainability; banking sector; crisis resilience